2021
DOI: 10.1021/jacs.0c12911
|View full text |Cite
|
Sign up to set email alerts
|

β-Substituted Alkenyl Heteroarenes as Dipolarophiles in the Cu(I)-Catalyzed Asymmetric 1,3-Dipolar Cycloaddition of Azomethine Ylides Empowered by a Dual Activation Strategy: Stereoselectivity and Mechanistic Insight

Abstract: The catalytic asymmetric 1,3-dipolar cycloaddition reactions of azomethine ylides with various electron-deficient alkenes provide the most straightforward protocol for the preparation of enantioenriched pyrrolidines in organic synthesis. However, the employment of conjugated alkenyl heteroarenes as dipolarophiles in such protocols to afford a class of particularly important molecules in medicinal chemistry is still a great challenge. Herein, we report that various β-substituted alkenyl heteroarenes, challengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 79 publications
0
26
0
Order By: Relevance
“…Recently, the Wang group overcame this hurdle by using β-substituted alkenyl heteroarenes 8 and a bulky monodentate phosphoramidite ligand (L*) to develop an efficient Cu(I)-catalyzed asymmetric 1,3-dipolar cycloaddition to form 10. 4 Professor Wang invited us to unmask the unclear origin of this high reactivity as well as their observed excellent enantioselectivity and exclusive diastereoselectivity. We then carried out an extensive computational study to decipher the mechanism and the origin of the stereochemistry, including the size effect of the ligand and substrates on the stereochemistry (Figure 3).…”
Section: Computational Predictions Of Enantio-and Regioselectivity Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Wang group overcame this hurdle by using β-substituted alkenyl heteroarenes 8 and a bulky monodentate phosphoramidite ligand (L*) to develop an efficient Cu(I)-catalyzed asymmetric 1,3-dipolar cycloaddition to form 10. 4 Professor Wang invited us to unmask the unclear origin of this high reactivity as well as their observed excellent enantioselectivity and exclusive diastereoselectivity. We then carried out an extensive computational study to decipher the mechanism and the origin of the stereochemistry, including the size effect of the ligand and substrates on the stereochemistry (Figure 3).…”
Section: Computational Predictions Of Enantio-and Regioselectivity Re...mentioning
confidence: 99%
“…Our DFT study (using the M06-2X, B3LYP-D3, PBE0, and ωB97X-D functionals) showed that the reaction generally follows a two-step mechanism with the second C−C bond formation as the rate-determining step to give the cyclization product. 4 When the monodentate ligand L* was employed, uncommon dual activation/coordination of both substrates (8 and 9) by the metal was elucidated computationally. The absence of additional coordination of substrate 8 raised the computed barrier and reduced the computed stereoselectivities.…”
Section: Computational Predictions Of Enantio-and Regioselectivity Re...mentioning
confidence: 99%
“…It is well known that the dipolarophiles of the 1,3-dipolar cycloaddition of azomethine yilde are generally limited to highly activated olefins bearing strong electron withdrawing substituents, [29][30][31][32][33][34] and only a few cases are associated with less reactive olefins, however, the utilization of inactive alkenes as dipolarophiles remains a great challenge. [70][71][72] In addition, the potential elimination of fluorine atoms in intermediates or products is another challenge for this reaction design. 73 Please do not adjust margins Please do not adjust margins…”
Section: Introductionmentioning
confidence: 99%
“…In view of the importance of deuterium-labelled chiral N-heterocycles and our continuing interest in the catalytic asymmetric construction of enantioenriched pyrrolidine derivatives with azomethine ylide, 31,41,42 we envisioned that merging the H/D-exchange (H/D-Ex) protocol 15 with the 1,3-dipolar cycloaddition reaction would meet this great challenge in a catalytic asymmetric manner and exactly cater for the ever-growing demand of deuterated bioactive heterocyclic molecules in the pharmaceutical industry. 43 As shown in Scheme 1b, we proposed that base-promoted and/or transition metal-catalyzed H/D-exchange of readily available glycine-derived aldimine ester with certain deuterium reagent would deliver the corresponding deuterated intermediate 1 - d n ( n = 1 or 2); 44,45 the deuterated aldimine ester could coordinate with the transition-metal cation to form the key N -metallated azomethine ylide bearing a deuterium atom at the α-position.…”
Section: Introductionmentioning
confidence: 99%